1990
DOI: 10.1016/0092-8674(90)90371-k
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal frameshifting in the yeast retrotransposon Ty: tRNAs induce slippage on a 7 nucleotide minimal site

Abstract: Ribosomal frameshifting regulates expression of the TYB gene of yeast Ty retrotransposons. We previously demonstrated that a 14 nucleotide sequence conserved between two families of Ty elements was necessary and sufficient to support ribosomal frameshifting. This work demonstrates that only 7 of these 14 nucleotides are needed for normal levels of frameshifting. Any change to the sequence CUU-AGG-C drastically reduces frameshifting; this suggests that two specific tRNAs, tRNA(UAGLeu) and tRNA(CCUArg), are invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
284
1
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(298 citation statements)
references
References 58 publications
11
284
1
2
Order By: Relevance
“…The observation that rare codons are a component of the MIE suggests a means through which translation and decay of the AL4ToLl mRNA may be coupled. It has been shown that in some cases rare codons can slow elongation rates along an mRNA and cause ribosomal pausing (4,8,33,38,42). Moreover, nonuniform translation rates along individual mRNAs have been implicated as being important in a number of cellular processes, including protein secretion, frameshifting, transcriptional attenuation, and protein folding (2,4,11,39,43).…”
Section: Discussionmentioning
confidence: 99%
“…The observation that rare codons are a component of the MIE suggests a means through which translation and decay of the AL4ToLl mRNA may be coupled. It has been shown that in some cases rare codons can slow elongation rates along an mRNA and cause ribosomal pausing (4,8,33,38,42). Moreover, nonuniform translation rates along individual mRNAs have been implicated as being important in a number of cellular processes, including protein secretion, frameshifting, transcriptional attenuation, and protein folding (2,4,11,39,43).…”
Section: Discussionmentioning
confidence: 99%
“…the retroviral gag and pol genes (Farabaugh et al, 1993); e.g. the retrotransposon TYA and TYB genes (Belcourt and Farabaugh, 1990); (ii) regulating gene expression, e.g. the Escherichia coli prfB gene (e.g.…”
Section: Biological Consequences Which Could Be Associated With the Pmentioning
confidence: 99%
“…3,4 While Gag can be readily translated as an immature Gag-p49 form, Pol synthesis requires a ribosomal frameshift, creating a template for the production of a Gag-Pol fusion protein that is further processed by proteolysis. 5,6 Similar to retroviruses, Ty1 genomic RNA, Gag and unprocessed Gag-Pol assemble to form immature VLPs. 7 VLP maturation, including the proteolytic conversion of Gag-p49 into Gag-p45 and the precise cleavage of GagPol, both achieved by a protease function contained in Pol, is a prerequisite for Ty1 RNA reverse transcription and transposition.…”
Section: Introductionmentioning
confidence: 99%